2021
DOI: 10.1016/j.heliyon.2021.e07250
|View full text |Cite
|
Sign up to set email alerts
|

Methods of green synthesis of Au NCs with emphasis on their morphology: A mini-review

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 122 publications
(162 reference statements)
0
2
0
Order By: Relevance
“…The nanoparticles demonstrated a wide range of forms, such as spheres, triangles, and quasi-hexagons, which present a favorable potential for utilization in the hemoglobin or protein electrochemistry . In addition, it has been observed that Rhodobacter capsulatus , a bacterium capable of photosynthesis, exhibits an enhanced ability to adsorb HAuCl 4 and demonstrates the capability to reduce trivalent gold . The involvement of carotenoids and NADPH-dependent enzymes, whether integrated into plasma membranes or discharged into the extracellular environment, has been recognized as crucial in the biosorption and bioreduction mechanisms of Au 3+ to Au 0 .…”
Section: Green and Sustainable Nanoparticle Synthesis: A Promising Sh...mentioning
confidence: 99%
See 1 more Smart Citation
“…The nanoparticles demonstrated a wide range of forms, such as spheres, triangles, and quasi-hexagons, which present a favorable potential for utilization in the hemoglobin or protein electrochemistry . In addition, it has been observed that Rhodobacter capsulatus , a bacterium capable of photosynthesis, exhibits an enhanced ability to adsorb HAuCl 4 and demonstrates the capability to reduce trivalent gold . The involvement of carotenoids and NADPH-dependent enzymes, whether integrated into plasma membranes or discharged into the extracellular environment, has been recognized as crucial in the biosorption and bioreduction mechanisms of Au 3+ to Au 0 .…”
Section: Green and Sustainable Nanoparticle Synthesis: A Promising Sh...mentioning
confidence: 99%
“… 76 In addition, it has been observed that Rhodobacter capsulatus , a bacterium capable of photosynthesis, exhibits an enhanced ability to adsorb HAuCl 4 and demonstrates the capability to reduce trivalent gold. 77 The involvement of carotenoids and NADPH-dependent enzymes, whether integrated into plasma membranes or discharged into the extracellular environment, has been recognized as crucial in the biosorption and bioreduction mechanisms of Au 3+ to Au 0 . 78 These processes occur both internally and externally in bacterial cells.…”
Section: Green and Sustainable Nanoparticle Synthesis: A Promising Sh...mentioning
confidence: 99%
“…The corresponding synthetic procedure is generally divided into two parts: The intracellular biosynthesis and the extra-cellular biosynthesis. The results seem to be very promising, but the experimental protocols require some improvement to optimize these innovative and green synthetic approaches [ 40 , 41 ].…”
Section: Au Nanomaterialsmentioning
confidence: 99%
“…In order to deepen the topic, we suggest several particularly meaningful reviews and papers [ 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ], including an interesting example of a hybrid organic–inorganic metal nanoparticles application to develop a localized surface plasmon resonance (LSPR)-based biosensor for antibiotics detection [ 47 ].…”
Section: Au Nanomaterialsmentioning
confidence: 99%